Alpha 1 antitrypsin (PI) phenotypes in two rheumatic diseases: a reappraisal of the association of PI subtypes in rheumatoid arthritis. Issue 1 (January 1989) - Papiha, S S; Pal, B; Walker, D; Mangion, P; Hossain, M A
Abstract : alpha 1 Antitrypsin phenotypes were determined by isoelectric focusing in 225 adult white patients with rheumatoid arthritis (RA), 60 patients with severe rheumatoid arthritis (grade III and IV), 17 sibling pairs--HLA identical but discordant for rheumatoid arthritis, and 122 random patients with Sjögren's syndrome. No significant increase in non-M phenotypes was found in either of the groups of patients with RA, but the association between M subvariants was striking. There was a significant increase in M1M2 phenotype and M2 allotype in both the RA and severe RA groups. This increase in M1M2 was also supported by DR4 positive patients with RA compared with DR4 positive siblings without RA. No apparent association of variant phenotype was found in four subgroups of patients with Sjögren's syndrome.